2003
DOI: 10.1046/j.1365-2672.2003.02076.x
|View full text |Cite
|
Sign up to set email alerts
|

Penicillium verrucosum in wheat and barley indicates presence of ochratoxin A

Abstract: Aims: The aims of this study were to isolate and identify ochratoxin A (OTA) producing fungi in cereals containing OTA and to determine the best selective and indicative medium for recovery of OTA producing fungi. Methods and Results: Seventy-six wheat, barley and rye samples from Europe containing OTA and 17 samples without OTA were investigated using three different media, dichloran yeast sucrose agar (DYSG), dichloran rose bengal yeast extract sucrose agar (DRYES) and dichloran 18% glycerol agar (DG18). Hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(100 citation statements)
references
References 19 publications
5
90
0
5
Order By: Relevance
“…% (Figure 2). This is in accordance with Lund & Frisvad [15], who suggested that microbial interactions in the grain and microbial interactions with their environment are responsible for this lack of correlation. Some kernels and spikelets were most likely not infected by the fungus but merely surface contaminated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…% (Figure 2). This is in accordance with Lund & Frisvad [15], who suggested that microbial interactions in the grain and microbial interactions with their environment are responsible for this lack of correlation. Some kernels and spikelets were most likely not infected by the fungus but merely surface contaminated.…”
Section: Discussionsupporting
confidence: 92%
“…All plates were incubated for 7 days at 25°C. The kernels were not surface-disinfected prior to plating, because P. verrucosum is sensitive to this procedure [15]. Based on its terra-cotta coloured reverse, the number of kernels colonized by P. verrucosum were enumerated.…”
Section: Enumeration Of P Verrucosum Contaminated Kernelsmentioning
confidence: 99%
“…Ambient drying systems in damp autumns require longer drying and this can result in the layers of the drying grain reabsorbing moisture and allowing the mycotoxigenic mould to become established. It is also a very competitive species and able to dominate under conducive environmental conditions in the stored grain 73 . Some studies have suggested that the level of contamination by P. verrucosum is a good indication of potential contamination with ochratoxin A 70,72,91 .…”
Section: Cereals and Ochratoxin A Contaminationmentioning
confidence: 99%
“…Ochratoxin A is produced by several fungal species in the Penicillium and Aspergillus genera, primarily Penicillium verrucosum, Aspergillus ochraceus and Aspergilli of the section Nigri, especially A. carbonarius (EFSA 2006). While P. verrucosum is the main OTA producer in cereals (Lund & Frisvad 2003), Aspergillus species such as A. ochraceus and A. carbonarius are typically associated with coffee, species and grapes (JECFA 2001). Among these species, A. carbonarius is considered to be a major source of OTA in grapes and wine (Serra et al 2003;Sage et al 2004).…”
mentioning
confidence: 99%